Extracting of temporal patterns from data for hierarchical classifiers construction - Szpyrka, M.; Szczur, A.; Bazan, Jan G.; Dydo, Ł. (IEEE, 2015)
A method of automatic extracting of temporal patterns from learning data for constructing hierarchical behavioral patterns based classifiers is considered in the paper. The presented approach can be used to complete the knowledge provided by experts or to discover the knowledge automatically if no expert knowledge is accessible. Formal description of temporal patterns is provided and an algorithm for automatic patterns extraction and evaluation is described. A system for packet-based network traffic anomaly detection is used to illustrate the considered ideas.
Praca opublikowana w: Szpyrka, M., Szczur, A., Bazan, J. G., & Dydo, L.: Extracting of temporal patterns from data for hierarchical classifiers construction. In Proceedings of the 2015 IEEE 2nd International Conference on Cybernetics (CYBCONF); Gdynia, Poland, 2015, June 24-26, IEEE, pages 330-335, Gdynia Maritime University, 2015
Keywords: LTL logic; feature extraction; hierarchical classifiers; network anomaly detection; temporal patterns